IMPACT OF ENVIRONMENTAL SANITATION AND INFECTION DISEASE AS A DETERMINING WASTING AGED 0-59 MONTHS IN ACEH BARAT DISTRICT - Khairunnas Khairunnas; Teuku Muliadi; Rona Arnisa; Enda Silvia Putri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Malnutrition is a public health problem in developing countries, with 50% of the 10-11 million children under five each year dying from preventable causes. West Aceh regency is known as the wealthiest district, but the wealth cannot necessarily overcome the problems of its people. This is indicated by discovering cases of malnutrition and malnutrition in the West Aceh Regency. Various efforts have addressed the nutritional issue, but the pain rate is still high. Purpose: This study aims to find out the relationship between environmental sanitation and infectious diseases with the nutritional status of toddlers in Meureubo Subdistrict, West Aceh Regency. Method: The type of research used is analytical survey research with a cross-sectional design. The sample was toddlers aged 0-59 months. The number of study samples of 95 people was taken by proportional random sampling method. Environmental sanitation variables were obtained from interviews with respondents using questionnaires and direct observations. Infectious disease variables were obtained from interviews with respondents. Variables bound to nutritional status are determined based on anthropometric measurements using the Weight/age indicator. The bivariate analysis uses chi-square and multivariate tests using logistic regression. Results: Statistical test results show that toddlers who do not have latrines will result in wasting in toddlers (95%CI:1.19-6.45), who do not have access to clean water (95% CI: 0.82-4.38), have a history of infectious diseases for the last three months (95% CI: 1.5- 8.5). From these results, we can conclude that the most significant influence on wasting is a child with a history of infectious diseases.